CORRELATION OF THE TRANSPARENCY PRINCIPLE WITH THE PRINCIPLES OF PUBLICITY AND OPENNESS IN THE ACTIVITIES OF ADMINISTRATIVE COURTS - Fedorenko, Yevhen (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of this article is to propose an approach for determining the relationship between the principle of transparency and the principles of publicity and openness in the activities of administrative courts and, on this basis, to substantiate proposals for improving national legislation. Research methods: the work is based on the dialectical method of scientific knowledge in logical and semantic combination with the method of comparative analysis, logical and semantic method, method of generalisation and documentary analysis. Results: the article examines the essence and correlation of the principles of transparency, publicity and openness. It is concluded that the principle of transparency encompasses the principles of publicity and openness of administrative proceedings. This principle not only ensures that parties to court proceedings receive information provided by law, but also requires the administrative court to respond appropriately to relevant requests and maintain a continuous relationship with the parties during the consideration of a court case. The proposes to amend the legislation with a view to enshrining the right of a party to an administrative case, within the framework of the principle of publicity and openness, to receive information not only about the results of consideration of its case, but also about the results of its resolution. Discussion: analysing the content of general theoretical issues of public authorities, including the judiciary, from the perspective of the implementation and realisation of the principles of transparency, publicity and openness. It emphasises the key role of the concept of transparency in judicial administrative proceedings as a combination of requirements not only to ensure that participants in judicial administrative proceedings are informed and have the opportunity to influence the administrative court in a legal manner, but also to ensure that the administrative court responds to the appeal, which is a condition for the proper implementation of the principles of dispositivity, competition and official clarification of the circumstances of the case.